Pengaruh Struktur Aset, Growth Opportunity Dan Risiko Bisnis Terhadap Struktur Modal - Nur Azizah Basmar; Yusriadi Hala; Fihma Nur Awalia (STKIP Subang, 2025)
The Effect of Asset Structure, Growth Opportunity, and Business Risk on Capital Structure in Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange. This study aims to determine and analyze the influence of asset structure, growth opportunities, and business risk on capital structure in food and beverage manufacturing companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach, a method used to describe the company's condition through analysis based on quantitative data. The population used in this study is 45 food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The sampling method used in this study is purposive sampling, a technique for selecting data sources based on certain considerations or criteria. The data sources in this study are secondary data. The results of this study indicate that Asset Structure (X1) does not have a significant effect on Capital Structure in Food and Beverage Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (Y), Growth Opportunity (X2) does not have a significant effect on Capital Structure in Food and Beverage Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (Y) and Business Risk (X3) has an influence and significance on capital structure in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (Y).